PORTRAITS OF RELIGIOUS MODERATION IN THE SALAF PESANTREN EDUCATION SYSTEM IN INDONESIA - Lailiyatul Azizah (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2020)
In the history of the development of Islam, many faces of Islam have been tainted by understandings that are not actually from the teachings of Islam itself. Radicalism, liberalism, and extremism have created intolerance and terrorism in the religion. The existence of Islam as a wasaṭiyah religion is an answer to the phenomena that occur in Islam as stated in the al-Qur’ān. Due to these waves of understandings, religious institutions or even the country were unable to position themselves as moderate institutions. Salaf pesantren are considered to be the only institutions that represent religious moderation in the Islamic revival century in Indonesia. The presence of the salaf pesantren is considered as a forum for negotiating Islamic identity as a wasaṭ wa i’tidāl religion and displays a polite and peaceful Islamic figure, by offering a salafiyah curriculum and kiai as the main actors in the management of the pesantren, as well as the role of pesantren graduates in social, religious and patriotic ontexts that are proven to carry a mission and moderate values ​​that can bring Indonesian Islam to become a peripheral.